2022
DOI: 10.3389/fcimb.2022.1020583
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum and colorectal cancer: From phenomenon to mechanism

Abstract: Colorectal cancer(CRC) is the third most frequent malignant tumor. The gut microbiome acts as a vital component of CRC etiology. Fusobacterium nucleatum(Fn) is a key member of colorectal cancer-associated bacteria. But we lack a systematic and in-depth understanding on its role in CRC evolution. In this article, We reviewed the abundance changes and distribution of Fn in CRC occurrence and development, potential effect of Fn in the initiation of CRC, the source of intratumoral Fn and the cause of its tropism t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 144 publications
0
8
0
Order By: Relevance
“…Considering that MMP7 plays an important role in F. nucleatum -induced CRC cell migration, we tried to find small molecule drugs that can target MMP7 for CRC patients with high MMP7 expression. According to reports, some natural drugs have inhibitory effects on F. nucleatum or F. nucleatum -activated signal pathways in CRC [ 36 ]. We built the MMP7- components Network by Cytoscape Software according to the data of HERB database (Additional file 3 : Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that MMP7 plays an important role in F. nucleatum -induced CRC cell migration, we tried to find small molecule drugs that can target MMP7 for CRC patients with high MMP7 expression. According to reports, some natural drugs have inhibitory effects on F. nucleatum or F. nucleatum -activated signal pathways in CRC [ 36 ]. We built the MMP7- components Network by Cytoscape Software according to the data of HERB database (Additional file 3 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms involved in the invasion and metastasis of cancer are complex and diverse, including epithelial-mesenchymal transformation, cytoskeletal remodeling, cell-cell adhesion, matrix destruction in the front of tumor invasion, and angiogenesis. Several previous studies have partially revealed the mechanisms underlying the role of Fusobacterium nucleatum in promoting CRC metastasis, such as the upregulation of metastasis-associated cytokines and chemokines, induction of epithelial-mesenchymal transition, regulation of cell adhesion-related molecules, and modulation of cytoskeletal proteins [ 36 ]. Here, our works initially found that MMP7 played a vital role in F. nucleatum -infection promoted CRC cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…The right and left colon are exposed to and have different compositions of intratumoral bacteria that vary along the colorectum. Studies have demonstrated the importance of the microbiome to the development, progression, or prognosis of CRCs 26–29 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the importance of the microbiome to the development, progression, or prognosis of CRCs. [26][27][28][29] Molecular mechanisms may account for the differences in CSS for RSCC and LSCC, as microsatellite instability (MSI), BRAF mutations, and RAS mutations have established predictive and prognostic genetic markers for colon cancer. 30,31 About 15% of all CRCs have mismatch-repair deficiency (dMMR), and pembrolizumab was shown to have a more favorable prognosis in RSCC than LSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation